Potential of subcritical water hydrolyzed soybean husk as an alternative biosorbent to uptake basic Red 9 dye from aqueous solutions (2022)
Bioethanol produced from lignocellulosic sources still faces problems related to the feasibility of this technological route. Within the biorefinery concept and clean technology, subcritical water hydrolysis (SWH) is efficient for dissociating lignocellulosic biomass. The solid co-products can be used for other applications to become SWH a more feasible process. The potential use of subcritical water hydrolyzed soybean husks (SWHSH) as a biosorbent to remove basic Red 9 dye (BR9) from aqueous solutions was evaluated in this study. SWHSH was efficient in the uptake of BR9, mainly at a pH of 8.0. The Langmuir model satisfied the biosorption equilibrium profile with a biosorption capacity of 56.8 mg g−1. The thermodynamic parameters indicate that the biosorption is spontaneous, with the ΔG0 ranging from − 22.08 to − 24.88 kJ mol1, with an endothermic nature (ΔH0 = 5.59 kJ mol−1). The biosorption equilibrium was in 60 min for all the initial concentrations studied. The Linear Driving Force (LDF) model fitted the data well, furnishing diffusivity values from 1.41 to 2.00 × 10−8 cm2 s−1. Desorption was also possible under acid conditions, and SWHSH could be effectively used 3 times. Last, the fixed-bed biosorption showed that the SWHSH could remove the BR 9 dye up to 180 min without regeneration, presenting a biosorption capacity of 46.1 mg g1 for 900 mL of treated effluent with an initial concentration of 200 mg L1. The characterization and biosorption results indicate that the BR9 tends to be adsorbed by physical forces, possibly by hydrogen bonds, electrostatic interaction, ππ interaction, and cation-π interaction. Overall, the SWHSH demonstrated potential application as a biosorbent for the removal of BR9.